(untitled) (Journal of Global Arts Studies, 2024)
Background: In today’s era of rapidly developing digital entertainment, the game industry has become one of the most dynamic and influential sectors within the global economy. As a core component of game production, game character design directly affects players’ gaming experiences and their recognition of a game. Among the various elements of character design, clothing plays a particularly significant role. Objective: This study aims to reveal the important role of clothing in game character design, summarize effective strategies and methods for costume application, and provide both theoretical support and practical guidance for game character design. At the same time, the study seeks to offer new perspectives and methodologies for interdisciplinary research while promoting the integration of art, design, psychology, and related disciplines. Methods: This research adopts a case study approach by selecting several representative games for in-depth analysis. Data are collected through literature review and observational analysis, while interviews, content analysis, and comparative analysis are employed to examine and summarize the functions and applications of clothing design in game characters. Results: The findings indicate that clothing plays a vital role in character design. It serves irreplaceable functions in cultural inheritance, character shaping, enhancement of player immersion and experience, and the strengthening of a game’s artistic appeal and market attractiveness. Conclusion: In the future development of clothing applications in game character design, creators should continue to pursue innovation while learning from outstanding domestic and international cases. Such efforts will further enrich game character design practices and contribute to the sustainable prosperity of China’s game industry.